Effects of Advanced Lighting Technology on Building Facades at Night, Emotional States and Behavioral Intentions Towards Urban Spaces - Moghaddam, Elyas Vahedi (2011)
The appearance of the physical environment can evoke strong emotions and affects spatial behavior. Static characters of contemporary urban spaces have low night life due to the lack of lighting quality of building facades. This study would like to position how building appearances can become an important factor that contributes towards enhancing urban spaces at night. In this respect, the current study aims to identify the influential traits of new lighting technology and reveal their effect on people emotional states and behavioral intention accordingly. The prominent characteristics of new lighting technology were recognized through investigating the related literature and examining the unique projects, which has used this technology. In next step, by employing a questionnaire-based survey, the Malaysian people’s evaluations of these attributes, their effect on emotional states and accordingly behavioral intention towards urban spaces was obtained. The item analysis and exploratory factor analysis of collected data presented visual quality and interactive quality as main influential factors of new lighting technology. Finally, the adapted M-R model which employed these qualities of new lighting technology as environmental stimuli was verified through Structural Equation Modeling. The decisive outcome supported our hypothesis which proves the importance of applying the new exterior lighting facade in the Malaysian context. The findings provided recommendations on how to increase visual qualities of building appearances, which will positively affect people’s preferences towards the built environment. The findings of the current study contribute to develop the theoretical foundation of physical environment’s effect on human psychology and behavior. In addition, the study contributes to develop the exterior lighting design criteria for decision making by identifying and categorizing the new attributes of exterior lighting, particularly in Malaysia. Applying these theoretical outcomes in order to develop a conventional system can assist designers, architects, and policy makers in increasing visual qualities of buildings appearances at night, which positively affect Malaysian people’s preferences for modern built environment correspondingly.